2015
DOI: 10.4103/1735-9066.170007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hope therapy on depression, anxiety, and stress among the patients undergoing hemodialysis

Abstract: Background:Renal failure is a major public health problem in the world. These patients experience high levels of psychological tension, anxiety, and depression, which leads to their lowered quality of life, increased health care costs, and early mortality. Due to medication side effects in these patients, non-medicational methods are more in demand now. This study aimed to investigate the effect of hope therapy on depression, anxiety, and stress among the patients undergoing hemodialysis.Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 12 publications
1
23
0
3
Order By: Relevance
“…For example, individualized counseling can be aimed at increasing hope. In one study of hemodialysis patients, a well-organized, regular counseling program helped those patients to frame their hope during their illness and to find ways to reduce anxiety and stress [ 26 ]. Fourth, we found that hope was at its minimum among patients at stage 5 CKD, that is, among patients whose disease was so severe that they almost needed dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individualized counseling can be aimed at increasing hope. In one study of hemodialysis patients, a well-organized, regular counseling program helped those patients to frame their hope during their illness and to find ways to reduce anxiety and stress [ 26 ]. Fourth, we found that hope was at its minimum among patients at stage 5 CKD, that is, among patients whose disease was so severe that they almost needed dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…These students are more humorous, less involved with their emotions (both positive and negative) and they use more problem-oriented coping methods to solve their problems. Hopeful students are less involved with common educational problems such as distraction, lack of social skills, helplessness, and disproportionate behaviors [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study [53] showed that patients' subjective hope for improvement can predict depression remission. Meisam Rahimipour [54] found that a high level of hope can protect those individuals' renal failure from occurrence and the relapse of depression. Thus, possibly, enhancing the level of hope, especially "positive readiness and expectancy", was one of the important ways to decrease the depressive symptoms of oral cancer patients in China.…”
Section: Discussionmentioning
confidence: 99%